2016
DOI: 10.1002/adma.201600594
|View full text |Cite
|
Sign up to set email alerts
|

Employing Lead Thiocyanate Additive to Reduce the Hysteresis and Boost the Fill Factor of Planar Perovskite Solar Cells

Abstract: Lead thiocyanate in the perovskite precursor can increase the grain size of a perovskite thin film and reduce the conductivity of the grain boundaries, leading to perovskite solar cells with reduced hysteresis and enhanced fill factor. A planar perovskite solar cell with grain boundary and interface passivation achieves a steady-state efficiency of 18.42%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

19
373
3
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 510 publications
(412 citation statements)
references
References 67 publications
19
373
3
2
Order By: Relevance
“…The result is similar to the previous reports for MAPbI3 system, which suggested that most of the SCNwould evaporate during annealing and three dimension MAPbI3-x(SCN)x would be obtained. 29,30 Some other reports proposed that layered MA2Pb(SCN)2I2 would be formed rather than three dimension MAPbI3-x(SCN)x, whose XRD patterns are quite different from ours. 31,32 To make sure whether NH4SCN acts as a volatile additive, we tested the Fourier transform infrared spectra of perovskite materials with and without NH4SCN (Fig.…”
Section: Introductioncontrasting
confidence: 78%
“…The result is similar to the previous reports for MAPbI3 system, which suggested that most of the SCNwould evaporate during annealing and three dimension MAPbI3-x(SCN)x would be obtained. 29,30 Some other reports proposed that layered MA2Pb(SCN)2I2 would be formed rather than three dimension MAPbI3-x(SCN)x, whose XRD patterns are quite different from ours. 31,32 To make sure whether NH4SCN acts as a volatile additive, we tested the Fourier transform infrared spectra of perovskite materials with and without NH4SCN (Fig.…”
Section: Introductioncontrasting
confidence: 78%
“…3C and D show the cut-off binding energy (E cut-off ) and Fermi edge (E F,edge ), respectively, of Lidoped P3HT. 41,42 It is known that the larger grains of the perovskite suppressed the charge traps at the grain boundaries, thereby, the R s was lowered and the hysteresis was mitigated. 40 Fig .…”
Section: Resultsmentioning
confidence: 99%
“…[20][21][22] Oxo-functionalized graphene (oxoG) and its reduced analogue are a novel 2D network structure materials with excellent electrical conductivity, desirable semiconducting properties, and superior chemical stability, which has been successfully utilized in the field of the solar cell, and memory devices. In this regard, ion migration inhibition can be achieved by passivating the grain boundary, regulating the crystal growth process or using additives to inhibit the movement of ions themselves.…”
Section: Introductionmentioning
confidence: 99%